Variables que influyen en el desarrollo de las competencias centrales, al requerir software en la empresa (Variables that influence the core competencies development, by requiring software in the company) - Cantú Mata, José Luis; Palomo González, Miguel Ángel; Segoviano Hernández, José; González Duéñez, Valeria Paola (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract: In this paper, we present a study in a business context, identifying the variables that influence the core competencies development and help to generate a competitive advantage. The literature review identifies variables that, in principle, help a company to innovate, sustainability, survival, and compete in the market. We propose a research model and then perform field work and analysis of results by pointing out the variables that are best represented in the research and make their respective discussion.